2020
DOI: 10.1098/rspa.2020.0056
|View full text |Cite
|
Sign up to set email alerts
|

Inert gas bubble formation in magnetron sputtered thin-film CdTe solar cells

Abstract: Cadmium telluride (CdTe) solar cells are deposited in current production using evaporation-based tech- niques. Fabricating CdTe solar cells using magnetron sputtering would have the advantage of being more cost-efficient. Here, we show that such deposition results in the incorporation of the magnetron working gas Ar, within the films. Post deposition processing with CdCl 2 improves cell efficiency and during which stacking faults are removed. The Ar then accumulates into clusters leadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
0
11
1
Order By: Relevance
“…Thus, it can be inferred that implanted Ar atoms form bubbles and reside near the surface of the TiO x layer, whose depth matches well with the projected range of Ar-ions, obtained from TRIDYN simulation. Formation of inert gas bubbles due to energetic implants in semiconductors is reported in the literature and leads to a reduction in the film density. In contrast, the SAED pattern obtained from the marked region on the Si substrate expectedly confirms its single crystalline nature (Figure C). In addition, energy dispersive X-ray (EDX) spectroscopic analysis (data not shown) reveals that the implanted region is highly oxygen deficient (Ti:O ≈ 1:1.25) and Ar atoms are present in the near-surface region of the implanted TiO x layer under consideration (i.e., T6), corroborating well with the XTEM results described above.…”
Section: Resultsmentioning
confidence: 60%
“…Thus, it can be inferred that implanted Ar atoms form bubbles and reside near the surface of the TiO x layer, whose depth matches well with the projected range of Ar-ions, obtained from TRIDYN simulation. Formation of inert gas bubbles due to energetic implants in semiconductors is reported in the literature and leads to a reduction in the film density. In contrast, the SAED pattern obtained from the marked region on the Si substrate expectedly confirms its single crystalline nature (Figure C). In addition, energy dispersive X-ray (EDX) spectroscopic analysis (data not shown) reveals that the implanted region is highly oxygen deficient (Ti:O ≈ 1:1.25) and Ar atoms are present in the near-surface region of the implanted TiO x layer under consideration (i.e., T6), corroborating well with the XTEM results described above.…”
Section: Resultsmentioning
confidence: 60%
“…In this study, we focus on semiconductors with the following three types of structures: rock salt ( Fm 3̅ m , #225), zinc blende ( F 4̅3 m , #216), and wurtzite ( P 6 3 mc , #186), which are wildly used inorganic solar cells. For simplicity, we only consider semiconductors with less than three types of elements . With these considerations, we find 3041 structures from the ICSD (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…36,37 The bubble formation owing to trapped Ar gas has been well studied for a CdTe precursor coated by a CdTe target. 38 Second, it was suggested that the blister could be formed owing to residual-stress relaxation, i.e., the internal stress formed in the metal-precursor film during DC sputtering could result in blister formation owing to the relaxation of compressive stress during the post-annealing process. 39,40 Therefore, the essential factor in the second model is the initial residual stress of the metal precursor.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To date, several models have been proposed for the blister-formation mechanism. First, it was suggested that the blisters (bubbles or buckling) formed owing to the release of trapped Ar gas, which is used as an inert working gas for coating the metal precursor film via sputtering. , The bubble formation owing to trapped Ar gas has been well studied for a CdTe precursor coated by a CdTe target . Second, it was suggested that the blister could be formed owing to residual-stress relaxation, i.e., the internal stress formed in the metal-precursor film during DC sputtering could result in blister formation owing to the relaxation of compressive stress during the post-annealing process. , Therefore, the essential factor in the second model is the initial residual stress of the metal precursor.…”
Section: Resultsmentioning
confidence: 99%